The #permendikbud30 Controversy Over the Prevention and Handling of Sexual Violence in Higher Education on Social Media - Irwa Rochimah Zarkasi; Cut Meutia Karolina; Muhammad Shaddam Rizqullah (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
The controversy over the Minister of Education and Culture Regulation (Permendikbudristek) Number 30 of 2021 on the Prevention and Handling of Sexual Violence in Higher Education is interesting to study. Criticism of this regulation, among others, Article 5, which Â carries Â the phrase â€œwithout the consent of the victimâ€, raises the meaning of legalizing immoral acts and consent-based free sex. Along with this polemic, reports and news about sexual violence in colleges have also emerged. This debate also occurs in society, especially with the presence of digital media, which makes a discourse grow fast and expand. Various comments and discussions occurred in various media, especially social media. This research using the concept of participatory culture aims to get an overview of public comments through the social media Twitter #permendikbud30, which contains uploads and comments regarding the controversy over Permendikbudristek Number 30 of 2021 and will be carried out through netnography studies. Finally, the results of the analysis show a picture of the diversity of peopleâ€™s perspectives in giving their opinions, namely: (a) by analogy with verses in the Quran; (b) there are many cases whose handling is not in favor of the victim and a firm law is needed; (c) educational institutions have not been responsive in handling cases that have occurred; (d) there is still polarization in politics, especially related to identity politics and (e) support for the relevant ministries for the ratification of this regulation is an important contribution to handling cases of sexual violence in the campus.